GUBENG STATION RAILWAY INFRASTRUCTURE PERFORMANCE ACCORDING TO USER PERCEPTION - Sulastri, Dwi; Wahyuni, Atik; Mudjanarko, Sri Wiwoho (ASTONJADRO, 2020)
Gubeng Station is the most populous station of 52 stations that enter the work area of PT KAI Daop 8 Surabaya, with 978,346 train passengers in January 2019, where this number is the highest number of train passengers for 3 years recorded at Gubeng station. Gubeng Station is also very unique, because it is located at a height of 5 meters and has two functionally different sides. The west side building is used for the departure and arrival of economy and express trains, while the east side building is for the departure and arrival of business and executive trains. This functional difference needs to be a study of the provision of infrastructure/facilities available at the Gubeng station whether it meets the minimum train service standards and has provided services/satisfaction and the importance of the existing facilities at the Gubeng station according to the train user perception. The method used is importance performance analysis (IPA) and the conclusion is that satisfaction and importance of the existing facilities at Gubeng station according to the train user perception obtained a satisfaction value of 2.48 which means that they still do not get maximum service and the average value of interest is 4.57 which means that the existing facilities at Gubeng station are needed by train passengers.